An Alternative Approach to Site Selection and Frequency for Global Positioning System Soil Mapping - Beard, F.R.; Koenig, R.T.; Miller, B.E. (Journal of Agricultural Systems, Technology, and Management, 2001)
A 2.5 acre research plot was utilized in an instructional project to evaluate alternative approaches to Global Positioning System (GPS) soil mapping. Based on detailed soil sampling data, a extensive record of cultural practices, and historical records of topographic and drainage alterations, the acreage was evaluated by a variety of methods, including grid and soil type sampling. Students visually inspected the property and were given four topographic maps that depict the land in different stages during 30 years of agricultural production. Information was provided concerning organic matter applications, crop production and yield results. Students proposed a sampling procedure and were provided results based on data previously collected. From this information, students recommended inputs and alterations to production procedures. The complete set of 1200 soil samples was utilized to determine the effectiveness of sampling procedures proposed by students.